2018
DOI: 10.3748/wjg.v24.i48.5462
|View full text |Cite
|
Sign up to set email alerts
|

Counteraction of perforated cecum lesions in rats: effects of pentadecapeptide BPC 157, L-NAME and L-arginine

Abstract: AIMTo study the counteraction of perforated cecum lesion using BPC 157 and nitric oxide (NO) system agents.METHODSAlongside with the agents’ application (after 1 min, medication (/kg, 10 mL/2 min bath/rat) includes: BPC 157 (10 μg), L-NAME (5 mg), L-arginine (100mg) alone or combined, and saline baths (controls)) on the rat perforate cecum injury, we continuously assessed the gross reappearance of the vessels (USB microcamera) quickly propagating toward the defect at the cecum surface, defect contraction, blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(127 citation statements)
references
References 46 publications
9
118
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] BPC 157 also acts as a free radical scavenger, counteracts free radical-induced lesions, and normalizes NO and MDA levels in tissues and during ischemia and reperfusion. 101,113,114,[116][117][118] Subsequent studies from other groups 2,96-101 have confirmed our original findings. [65][66][67][68][69][70][71][72][73][74][75][76][77][78] Pleotropic effects involving distinctive receptors, including VEGFR2 and growth hormone receptors, distinctive pathways, including VEGFR2-AKT-eNOS, ERK ½, FAK-paxillin, FoxO3a, p-AKT, p-mTOR and p-GSK-3β, and distinctive loops, including stimulation of the egr-1 gene and its corepressor gene naB2, and counteraction of increases in pro-inflammatory and procachectic cytokines, 2,[96][97][98][99][100][101] likely minimize the inherent lack of full understanding of the mechanisms that may be involved.…”
Section: Homeostasissupporting
confidence: 82%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] BPC 157 also acts as a free radical scavenger, counteracts free radical-induced lesions, and normalizes NO and MDA levels in tissues and during ischemia and reperfusion. 101,113,114,[116][117][118] Subsequent studies from other groups 2,96-101 have confirmed our original findings. [65][66][67][68][69][70][71][72][73][74][75][76][77][78] Pleotropic effects involving distinctive receptors, including VEGFR2 and growth hormone receptors, distinctive pathways, including VEGFR2-AKT-eNOS, ERK ½, FAK-paxillin, FoxO3a, p-AKT, p-mTOR and p-GSK-3β, and distinctive loops, including stimulation of the egr-1 gene and its corepressor gene naB2, and counteraction of increases in pro-inflammatory and procachectic cytokines, 2,[96][97][98][99][100][101] likely minimize the inherent lack of full understanding of the mechanisms that may be involved.…”
Section: Homeostasissupporting
confidence: 82%
“…1). While introducing a new concept BPC 157 first strictly follows, and then, it considerably extends, with recently demonstrated recruitment of blood vessels to bypass vascular occlusion, 101,113,117,118 the guidelines of classic of stomach cells/endothelium cytoprotection [14][15][16][17][18][19][20][21] and Selye's concept of stress response against stress injury to reestablish disturbed homeostasis. [22][23][24][25]40 Thus, in practice, these findings may be relevant to resolving Robert's cytoprotection/adaptive cytoprotection/organoprotection, [14][15][16][17][18][19][20][21] and consequently, Selye's stress coping response, [22][23][24][25]40 and practical applicability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations